Engineering Calculations for Catalytic Hydrolysis of CF4 - Robert Barat (ChemEngineering)
Tetrafluoromethane (CF4) is the simplest perfluorocarbon, a class of compounds with very high greenhouse gas potential. Catalytic hydrolysis offers an opportunity to convert these compounds to manageable CO2 and HF. Recently published data showed the effectiveness of Ga-doping to overcome the fluorine poisoning of various Al2O3 catalysts at relatively modest temperatures. This prior work offered a partial catalytic mechanism together with kinetic and conversion data. The current paper completes the catalytic mechanism, and then analyzes it using the Langmuir–Hinshelwood algorithm for both the initial CF4 conversion, and the catalyst site regeneration. The resulting derived rate expression, together with a catalyst activity coefficient expression, are then used in flow reactor configurations to simulate both relatively short exposure time runs with little loss of activity, as well as longer runs with severe activity loss. The reasonable agreement with the published laboratory data suggests that these expressions can be used for a larger-scale practical reactor design.